Possible Polygenic Tautological Factor Explaining the Brain Diseases that are Cosegregating in a Multigenerational Family from Antioquia (2024)
ABSTRACT: Background: Proper human embryonic and neurological development requires the concerted collaboration of a large network of genes in a spatially and temporally correct manner. Recent findings suggest that purely monogenic forms of neurodevelopmental disorders are the exception rather than the rule. A multigenerational family from Colombia with 149 individuals, presents 30 individuals affected or possibly affected with various brain diseases. We describe polymorphisms in different genes, which may potentially be associated with the phenotypes and propose the existence of an oligogenic interaction network that may explain a shared molecular and functional diagnosis. Methods: Clinical characterization of the phenotypes (medical, neurological, neuropsychological evaluations and brain magnetic resonance imaging). Whole exome sequencing was analyzed in 42 individuals, and variants were prioritized according to mode of inheritance, MAF<0.01, type, pathogenicity predictors, and phenotype-genotype relationship. Neurological and neuropsychological follow-ups and brain magnetic resonance imaging were performed. Structural and interaction analysis between proteins. Results: We performed a systematic review in search of pathogenic variants with neurological phenotypes, associated with the genes CTBP1 and CTBP2; relevant transcription factors in our initial data, with possible candidate variants in the study family. We identified and published a homozygous variant in three siblings from a nuclear family for the SPAG9 gene, a previously undescribed syndrome with neurodevelopmental impairment and neurodegeneration. We described a spectrum of nine distinct phenotypes that can be explained by variants in multiple genes with evidence of a shared genetic basis among them, pleiotropy and epistasis. Regulation of neuronal differentiation was the main biological process associated with 7 proteins involved. Conclusions: A protein interaction network that could explain a pleiotropic phenomenon in developmental diseases is identified in the family under study. The family studied can help to understand several different pathways or mechanisms involved in key processes for brain formation and human embryogenesis, and can help to elucidate previously unthought-of mechanisms. A clinical follow-up and a complete genealogy allowed us to go beyond the sole description of the individual mutations of each nuclear family, to understand the entire family as a possible alteration of shared biological pathways. The phenotypes of the exposed family and the logic that brought the research question, made us think of possible common pathways. This same thought applied to other families or individuals with various overlapping complex diseases, can be a multiplying effect to identify new unknown genetic functions and eventually, treatments for several diseases. Further analysis is required to determine a possible major gene, decipher the mechanisms involved and clarify the epigenetics role. These findings indicate the possibility of broader applicability to most inherited neurodevelopmental disorders.